2008
DOI: 10.1136/emj.2007.057661
|View full text |Cite
|
Sign up to set email alerts
|

Modified early warning score predicts the need for hospital admission and inhospital mortality

Abstract: The MEWS, specifically five selected parameters, may be used as a rapid, simple triage method to identify medical patients in need of hospital admission and those at increased risk of inhospital death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
189
3
6

Year Published

2010
2010
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(211 citation statements)
references
References 8 publications
13
189
3
6
Order By: Relevance
“…30 Although PEWS can identify patients at risk in the ED for ICU admission and, to a lesser extent, identify patients at risk for hospitalization, we do not advise using warning scores as triage tools to prioritize patients. 31 At present, there is no evidence that PEWS are better than conventional triage systems. To prove that PEWS as triage tools are better than conventional triage systems or that PEWS have added value to conventional triage systems, a direct comparison study should be conducted in which patient outcomes and costs are included.…”
Section: Discussionmentioning
confidence: 99%
“…30 Although PEWS can identify patients at risk in the ED for ICU admission and, to a lesser extent, identify patients at risk for hospitalization, we do not advise using warning scores as triage tools to prioritize patients. 31 At present, there is no evidence that PEWS are better than conventional triage systems. To prove that PEWS as triage tools are better than conventional triage systems or that PEWS have added value to conventional triage systems, a direct comparison study should be conducted in which patient outcomes and costs are included.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that hospital mortality can be predicted on the basis of illness severity scores calculated at the time of admission, either in the emergency department, 18,19 an assessment unit 20,21 or a medical ward. 22 None of these studies looked at whether the average early warning scores varied according to time or day of admission; although such scores are somewhat blunt tools, this analysis may be a useful next step to help our understanding of the variation in mortality we have observed.…”
Section: Patient and Pre-hospital Factorsmentioning
confidence: 99%
“…While clinical condition and acuity primarily influence the likelihood of admission, 3 non-medical factors may also contribute. [4][5][6][7][8][9][10][11][12][13] For the purpose of our study, non-medical refers to all factors, other than a patient's clinical condition, that potentially influence admission decisions.…”
Section: Introductionmentioning
confidence: 99%